PENDAPATAN DAN RISIKO USAHA TAMBAK UDANG WINDU DAN UDANG VANAME DI KECAMATAN PASIR SAKTI KABUPATEN LAMPUNG TIMUR - Yuni Astika Rahayu; Fembriarti Erry Prasmatiwi; Ani Suryani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The purposes of this study are to analyze income and risk of shrimp cultivation, factors affecting the income, and factors affecting land conversion from cultivating tiger shrimp to vaname shrimp. The study was conducted in Purworejo Village, Pasir Sakti Subdistrict, East Lampung District, in March - April 2017 using a survey method. Respondents were 60 farmers consisting of 30 vaname shrimp farmers and 30 tiger shrimp farmers taken randomly. Data processing uses income analysis, multiple linear regression analysis, coefficient of variation analysis, and logit analysis. The results showed that the income of vaname shrimp farming was Rp53,586,604.00/ha and of tiger shrimp was Rp6,818,543.00/ha. Tiger shrimp farming has a higher risk than vaname shrimp. The level of education, farm income, and shrimp prices are negatively affect the decision-making opportunities of farmers to switch from tiger shrimp farming to vaname shrimp.Keywords: income, risk, tiger shrimp, vaname shrimp